Community based sensitization to address maternal and child health problems in tribal population of India - Patil, Karan Shrikant; Lokhande, Vaishali; Agarwal, Bharat; Pendse, Manish; Misra, Anand (International Journal of Advances in Medicine, 2022)
Background: India fights with substantial maternal and child health (MCH) concerns, accounting about one quarter of the global burden of maternal and childhood mortality. The current study was tried to assess the impact of community partnerships between medical students, community stakeholders (TBAs and local tribal girls) and general community members on their awareness levels about MCH care and services. Methods: a community-based pilot interventional study was conducted at one of the rural blocks of Maharashtra state of India. Of 120, sixty (50%) first year undergraduate MBBS medical students (intervention group) posted at two months rural healthcare training programme’ participated in preparing MCH related health education material (HEM) in local language. Similarly local tribal girls, TBAs and general community people were trained about MCH and their knowledge levels were assessed. Results: Pre and post training assessment scores of participants (students, TBAs, tribal girls and general people) indicated significant (p<0.05) differences in their knowledge about MCH. The used approach of community collaborations in this study upgraded the knowledge of stakeholders (TBAs, tribal girls) and common tribal people about basic aspects of MCH and associated welfare schemes. The study also reported positive attitudes of all participants about an intervention. Conclusions: Productive and synergistic community partnerships can be created among health care providers, community health workers and other stakeholders to ensure commitment and engagement towards positive health.